Microcystic Changes in the Retinal Internal Nuclear Layer Associated with Optic Atrophy: A Prospective Study - Benjamin Wolff; Georges Azar; Vivien Vasseur; José-Alain Sahel; Catherine Vignal; Martine Mauget-Faÿsse (Journal of Ophthalmology)
Purpose. This study aimed at assessing the prevalence of pathologies presenting retinal inner nuclear layer (RINL) microcystic perimacular changes associated with optic nerve atrophy (OA). The charts of patients presenting a significant defect of the Retinal Nerve Fiber Layer (RNFL) were included prospectively in this study. Patients were classified according to the etiology of the RNFL defect. Two hundred and one eyes of 138 patients were enrolled in this analysis. Retinal images obtained showed the typical hyporeflective perifoveal crescent-shaped lesion composed of small round hyporeflective microcysts confined to the RINL in 35.3% of the eyes. Those findings were found in 75% of eyes presenting hereditary OA, 50% of eyes presenting ischemic optic neuritis, 50% of eyes with drusen of the optic nerve (ON), 44.4% of eyes presenting a compressive OA, 32% of eyes presenting inflammatory optic neuropathy from multiple sclerosis, 18.5% of eyes presenting OA from undetermined origin, and 17.6% of eyes having primary open-angle glaucoma. This study demonstrates that microcystic changes in RINL are not specific to a disease but are found in OA of various etiologies. Moreover, their incidence was found to be dependent upon the cause of OA, with the highest incidence occurring in genetic OA.